"Flos de radice Iesse". A Hermeneutic Approach to the Theme of the Lily in Spanish Gothic Painting of The Annunciation from Patristic and Theological Sources - Salvador González, José María (Eikón / Imago, 2013)
Contradicting the superficial and unjustified conventional interpretation of the lily in the images of the Annunciation, this paper proposes two new deep theological explanations of that flower in this biblical episode. Based on the analysis of an abundant amount of quotes of the Church Fathers and medieval theologians, which show a well- established doctrinal tradition about this issue, we will try to demonstrate that the stem of lilies at the scene of the Annunciation symbolizes both the Mary’s virginal divine motherhood and the supernatural human incarnation of God the Son, Christ. The current paper seeks also to relate these textual analyses of patristic and theological sources to twelve Spanish Gothic Annunciations which include a stem of lilies.